ORTHOGRAPHIES IN A RAPIDLY CHANGING WORLD: NEGOTIATED COMPROMISES BETWEEN SEVERAL PARTIES (The University of Nairobi Journal of Language and Linguistics, 2023)
The point of this paper is that orthography development for unwritten African languages in the 21stcentury requires input from two major fields of study: linguistics and the aspect of learning psychologyrelated to literacy. The second assumption this paper is built on is that orthography development is notstraightforward; it always involves compromises.In the past, writing systems had a chance to develop over centuries, as people tried tocommunicate in writing, and finding writing rules, which worked for them and their limited readership.Some African writing systems were initiated over twenty centuries ago. Egyptian hieroglyphs are evenolder than that, approximately dating from between 3000 BC and 400 AD(http://scriptsource.org/cms/scripts/page.php?item_id=script_detail&key=Egyp). Other ancientexamples are Ethiopic, Tifinagh, and Vai. Most were unique inventions(http://scriptsource.org/cms/scripts/page.php?item_id=entry_detail&uid=dvm6v7yblj).In the 21st century, however, the world of literacy has changed dramatically from the time of claytablets and styluses. A select few readers were taught to read then. This is the age of EFA (UNESCO’SEducation for All, 2000-2015) literacy goals for the masses. Book publishing is proliferating for minoritylanguage groups, even on laptops and cellphones. (http://www.nbcnews.com/tech/mobile/mobilephones-promote-literacy-poorest-countries-un-report-n88151). This means that the world’s unwrittenor unstandardized writing systems will require focused and time-sensitive attention from two disciplines:linguistics and the aspects of learning psychology that are related to literacy. Standardization takes time:orthographies develop in stages as literature is developed and used (Karan, 2014). So how can the processbe expedited, while the potential readership, speakers of the unwritten language, have yet to possessadvanced reading skills? We no longer have time to develop orthographies over centuries.This paper describes the roles of linguists, educators and the major stakeholders, as well as theorthography users. It also describes the elements of language which compete for representation in Africanwriting systems. Section 2 defines orthography outcomes while section 3 describes the process oforthography development; section 4 sheds light on the work of the linguist and the literacy consultant;section 5 discusses the tension between linguistic analysis and readability, and the paper is concluded insection 6.